Health‐related quality of life in a randomized trial of neoadjuvant chemotherapy or chemoradiotherapy plus surgery in patients with oesophageal cancer (NeoRes trial). Issue 11 (22nd August 2019) - Sunde, B.; Klevebro, F.; Johar, A.; Johnsen, G.; Jacobsen, A.‐B.; Glenjen, N. I.; Friesland, S.; Lindblad, M.; Ajengui, A.; Lundell, L.; Lagergren, P.; Nilsson, M.
Abstract : Background: There are few data comparing health‐related quality of life (HRQoL) after neoadjuvant chemotherapy alone (nCT) compared with neoadjuvant chemoradiotherapy (nCRT) in patients with oesophageal cancer. Methods: In the NeoRes trial, patients were assigned randomly in a 1 : 1 ratio to receive either cisplatin 100 mg/m 2 on day 1 and an infusion of 750 mg per m 2 5‐fluorouracil over 24 h on days 1–5 in three 21‐day cycles (nCT) or the same chemotherapy regimen, but with the addition of 40 Gy radiotherapy (nCRT). HRQoL data were collected at baseline, after neoadjuvant therapy and at 1, 3 and 5 years after surgery. The European Organisation for Research and Treatment of Cancer (EORTC) core questionnaire QLQ‐C30 and disease‐specific modules were used. Results: Of 181 patients randomized, 165 were included in the analysis of HRQoL. In a direct comparison between the allocated treatments, odynophagia after completion of neoadjuvant therapy but before surgery ( P = 0·047) and troublesome coughing at 3 years' follow‐up ( P = 0·011) were more pronounced in the nCRT arm. In the longitudinal analyses within each treatment arm, a large deterioration in HRQoL was noted at 1 year. Some recovery was seen in both arms over time but, after 3 and 5 years, patients in the nCRT arm reported more symptoms compared with baseline than patients in the nCT arm. Conclusion: HRQoL after multimodal treatment for cancer of the oesophagus or gastro‐oesophageal junction was impaired and more pronounced in patients who underwent nCRT, with only partial recovery over time. Abstract : Analysis of health‐related quality of life in the NeoRes trial found that patients allocated to neoadjuvant chemoradiotherapy (nCRT) reported more symptoms at 3 and 5 years' follow‐up compared with those who had neoadjuvant chemotherapy (nCT) for oespophageal cancer. More impairment after chemoradiation Abstract : Antecedentes: Se dispone de poca información sobre la calidad de vida relacionada con la salud ( health‐related quality of life, HRQOL) en pacientes con cáncer de esófago después de quimioterapia neoadyuvante sola en comparación con quimiorradioterapia neoadyuvante. Métodos: En el ensayo NeoRes, los pacientes fueron asignados de forma aleatoria 1:1 a tratamiento con cisplatino 100 mg/m 2 en el día uno y 5‐Fluorouracilo 750 mg/m 2 /infusión de 24 horas en los días 1‐5 en tres ciclos de 21 días (nCT) o al mismo régimen de quimioterapia, pero con la adición de radioterapia 40 Gy (nCRT). Los datos de HRQOL se recogieron al inicio, tras el tratamiento neoadyuvante y al cabo de 1, 3 y 5 años tras la cirugía. Se utilizaron los cuestionarios QLQ‐C30 de la European Organisation for Research and Treatment of Cancer (EORTC) y los módulos específicos para la enfermedad. Resultados: De 181 pacientes aleatorizados, 165 fueron incluidos en el análisis de la HRQOL. En la comparación directa entre los tratamientos asignados, la odinofagia tras terminar nCRT pero antes de la cirugía ( P = 0, 047) y la tos molesta a los 3 años de seguimiento ( P = 0, 011), fueron más acentuadas en el brazo de nCRT. En el análisis longitudinal dentro de cada rama de tratamiento hubo un fuerte deterioro en la HRQOL al año. Se observó cierta recuperación en ambas ramas con el tiempo, pero a los 3 y 5 años de seguimiento, los pacientes de la rama de nCRT describieron más síntomas en comparación con la situación de inicio que los pacientes de la rama de nCT. Conclusión: La HRQOL después del tratamiento multimodal del cáncer de esófago o de la unión gastroesofágica se ve afectada, siendo dicha afectación más pronunciada en pacientes que recibieron nCRT, recuperándose solo parcialmente con el tiempo.